Volume 2B: Thermal Hydraulics 2014
DOI: 10.1115/icone22-30675
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Flow Characteristics for an Open Natural Circulation System

Abstract: An open natural circulation system applied to the passive containment cooling system is proposed for the large dry double-wall concrete containment after severe accidents. In order to investigate the operating behaviors of the open loop, a numerical code is developed to simulate the transient flow characteristics from the startup to the long-term operation. The results show that the open system may experience such four stages as startup process, quasi-steady single-phase flow, transition stage and quasi-steady… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Former research about flow instability has focused on closed natural circulation, but relatively few studies on the open natural circulation loop. Guo et al conducted experiments to reveal the flow instability phenomenon and its mechanism during the start-up process and a classification of flow instability is also given [18,19]. Hou et al found the law of changes in flow patterns under the condition of different start-up power through experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Former research about flow instability has focused on closed natural circulation, but relatively few studies on the open natural circulation loop. Guo et al conducted experiments to reveal the flow instability phenomenon and its mechanism during the start-up process and a classification of flow instability is also given [18,19]. Hou et al found the law of changes in flow patterns under the condition of different start-up power through experiments.…”
Section: Introductionmentioning
confidence: 99%